Strategies For The Development Of The Suladaha Beach Tourism Area To Increase Local Revenue In The City Of Ternate - Grietha Emelia Karambut; Siti Nur Janna Tuanany; Ayu Widowati Johannes (Post Graduate School of Government Science, 2026)
On the PAD data of Ternate City from 2020 until 2024, tourism sector only contributed a number of around 0.29 per cent while in addition to Ternate they have coastal assets with high qualityThis irony shows that much better; This research study the strategy of developing Sulamadaha Beach as a tourism area and its implication to fiscal performance. Grounded on Sustainable Tourism Development theory and Strategic Management theory, the paper proposes a integrated metric-based fiscalstrategic model linking a quantitative IFAS–EFAS analysis (the results of a SWOT retrospective mapped within an IFAS and EFAS matrix) to destination-level fiscal indicators associated with operational policy alternatives. The analysis is a descriptive qualitative, data were obtained from semi-structured interviews with twelve informants (echelons of the Ternate City Tourism Office, local tourism awareness group, business actors, visitors and residents), field observations and documentation; and aquaculated using source presenting triangulation methods as well as theory triangulation member checkings audit trail. The strategic position of Sulamadaha is in Quadrant I with an aggressive strategy: IFAS score = 0.66 and EFAS score = 0.83 where the strategic theme refers to glass-beach branding; a communitybased marine tourism programme, subterranean zeitgeist delivery via e-ticketing at tiered entrance fee Sulamadaha's Rp. 5,055 per visitor revenue efficiency cannot boast against freeentrance destinations. Revenue = V × t × (1–e) with 25,986 visits in 2024, across Rp. 5,000–10,000 tariff assumptions and 0–15 percent elasticity assumptions yields maximum potential entrance-fee receipts of Rp. 110. 4259. 9 million per year. These are not predictions of the future, but rather simulated policy scenarios.